Effect of Different Irrigating Solutions on the Apical Sealing Ability of Resin Based Root Canal Sealer - Syed Saqib Raza Naqvi; Syed Yawar Ali Abidi; Affan Ahmed; Naheed Najmi; Muhammad Atif Saleem Agwan; Anosha Saqib (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
ABSTRACT Objective: To assess the effect of different irrigating solutions (Normal saline, 5.25% NaOCl and 90% Ethanol) on apical sealing ability of resin based root canal sealer filled with single cone obturating technique in extracted teeth.  Methods: From March 2022 to September 2022, the Case Control research was carried out  in Karachi. Sample size of 30 single root teeth were decoronated and roots were divided into Group A and B Group B is subdivided into two cases according to the type of irrigating solution used. Group A irrigation solutions include 5ml of  Normal saline solution, while group B includes 5ml of 5.25% Sodium Hypochlorite and 5ml of 90% Ethanol, solution. Teeth were prepared, obturated, placed in 2% methylene blue dye and extent of dye penetration was done under a Digital stereomicroscope and maximum leakage was measured by using software. Data was analyzed on SPSS version 26.0. Results:  All solutions were normally distributed. While comparing both groups, Ethanol has the lowest mean value of dye penetration i.e. 1.07 ± 0.63 which means that this irrigating solution has least microleakage  and provide effective seal of resin  sealer to the root canal wall filled by using single cone obturating technique. Case group irrigation solutions has significant p- value i.e. 0.000 which indicates absolute absence of microleakage. Comparison of mean value of sodium hypochlorite and ethanol, ethanol is more efficient irrigation solution as it has shown least dye penetration as compare to sodium hypochlorite. Conclusion:  It has been concluded that among all the solutions, Ethanol has proved to be the most effective irrigation solution followed by Sodium hypochlorite showed least dye penetration and hence least microleakage.